Ensino de Filosofia no Brasil: a repercussão das reformas da educação na disciplina de Filosofia - Vieira, José Vanucci Evaristo (2024)
The research investigates the effects of educational reforms on the teaching of Philosophy in Brazil, especially in the New High School (NMS), through an approach that uses bibliographical analysis and experience reports. It begins with the historical trajectory of philosophy teaching, from colonisation to the current context. The instability and exclusion of philosophy from curricula throughout Brazilian history is analysed, which has had a negative impact on the country's critical and democratic education. The study analyses the challenges faced by secondary education in Brazil, highlighting educational reform, the National Common Curriculum Base (BNCC) and the New Secondary Education Law. It highlights the dilution of Philosophy into generic competences and the devaluation of the subject, a reflection of neoliberal policies that prioritise technical and market training to the detriment of critical thinking. The study highlights the resistance of students, teachers and the philosophical community to these changes. It concludes with the impact of the reform, which has generated uncertainty about the position and importance of philosophy, emphasising the need to preserve its relevance in the Brazilian educational scenario.